Răspunsuri

Cel mai inteligent răspuns!
2014-10-14T10:30:21+03:00
A)32;16+{76-2x[(20+4x5);5]-2x6}=            b)(3+6+9+12+15+18);(1+2+3+4+5+6)=

32;16+{76-2x[(20+20);5]2x6}=
32;16+[76-2x(40:5-2x6)]=
32;16+(76-2x8-12)=
32;16+(76-16-12)=
32;16+(92-12)=
32;16+80=
8+80=
88

b)(3+6+9+12+15+18);(1+2+3+4+5+6)=
(9+21+33);(3+7+11)=
(30+33);(10+11)=
63;21=


c)3+10x[3+10x[126+10x(24+24;2-6)]}-42600=
3+10x[3+10x[126+10x(24+12-6)]}-42600=
3+10x{3+10x[126+10x(24+6)]}-42600=
3+10x[3+10x(126+10x6)]-42600=
3+10x[3+10x(126+60)]-42600=
3+10x(3+10x186)-42600=
3+10x(3+1860)-42600=
3+10x1863-42600=
3+18630-42600=
18633-42600=imposibil de rezolvat 
La punctul a) ai gresit la calcule!
32:16+(76-16-12)=32:16+(60-12)=32:16+48=2+48=50